Investigating the Impact of Task-Based Learning in Writing Skill of EFL Undergraduate Students at Indonesian University - Eka Sari, Septi Fani; Basya, Dihliza; Ismaili, Ismaili (Linguapedia, 2023)
The popularity of Task-Based Learning (henceforth, TBL) approach has risen the effectiveness in enhancing learners’ competence, since it was proposed in 1980s. However, there has been limited research about investigating participants’ writing skill with TBL-mediated in EFL domain. This study investigated the impact of TBL in writing skill of undergraduate students at Indonesian University. This present study employs a qualitative interview study to declare the result of impact of utilizing TBLT as approach which assist to boost the undergraduate students’ writing skill. Fifteen participants from a private university in Jember, Indonesian are voluntarily involved and subsequently interviewed in this research. Datal were collectedl through lsemi-structured interviewsl to get in-depth information with respect to their experiences related to the impact of utilizing TBLT in their writing skill. Based on the data finding Task-Based Language Teaching (TBLT) has a positive impact on undergraduate students' writing skills in the English as a Foreign Language (EFL) domain. TBLT provides students with authentic and meaningful writing tasks that help them develop their writing skills in a practical context. TBLT also promotes students' engagement, motivation, and collaboration, which are essential factors in improving writing proficiency.